2014
DOI: 10.1007/s12192-013-0484-1
|View full text |Cite
|
Sign up to set email alerts
|

T cell recognition of naturally presented epitopes of self-heat shock protein 70

Abstract: Self-reactive T cells have shown to have a potential role as regulators of the immune system preventing or even suppressing autoimmunity. One of the most abundant proteins that can be eluted from human HLA molecules is heat shock protein 70 (HSP70). The aims of the current study are to identify HSP70 epitopes based on published HLA elution studies and to investigate whether T cells from healthy individuals may respond to such self-epitopes. A literature search and subsequent in silico binding prediction based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 56 publications
0
7
0
Order By: Relevance
“…They adoptively transferred the Mtb B29-specific Tregs and were able to show that these mycobacterial epitope-specific Tregs suppressed ongoing experimentally induced arthritis in mice. In a separate study, peptides H161 and H167, derived from the most conserved region of HSP70 (both among species and among human HSP70 variants), showed strong recognition by PBMCs of healthy humans; T cell proliferation, gamma-interferon production and IL-10 secretion were reported [45]. More recently, peptides derived from HSP "BiP" were shown to include T cell proliferation, IL-10 expression, and to reduce inflammation in a murine model [46].…”
Section: Redundancy and Regulation Of T Cell Responsementioning
confidence: 96%
“…They adoptively transferred the Mtb B29-specific Tregs and were able to show that these mycobacterial epitope-specific Tregs suppressed ongoing experimentally induced arthritis in mice. In a separate study, peptides H161 and H167, derived from the most conserved region of HSP70 (both among species and among human HSP70 variants), showed strong recognition by PBMCs of healthy humans; T cell proliferation, gamma-interferon production and IL-10 secretion were reported [45]. More recently, peptides derived from HSP "BiP" were shown to include T cell proliferation, IL-10 expression, and to reduce inflammation in a murine model [46].…”
Section: Redundancy and Regulation Of T Cell Responsementioning
confidence: 96%
“…One of the first recognized functions of heat shock proteins (HSPs) is to chaperone other proteins, and most of them are upregulated during stressful conditions. Moreover, extracellular HSPs participate in the induction of cellular immune responses since they are involved in the antigen processing and presentation ( de Jong et al , 2014 ). HSP70s are one of the most abundant sources of HLA class II ligands.…”
Section: Pemphigus Geneticsmentioning
confidence: 99%
“…These findings demonstrate a complex relationship between autoimmunity and AD: natural autoimmunity to HSP70 is associated with health, whereas altered autoimmunity to HSP70 is related to disease. In this way, HSP70 could be essential autoantigens in balancing the healthy immune system (de Jong et al, 2014).…”
mentioning
confidence: 99%
“…(Bouchier-Hayes et al, 2010;Murapa, Ward, Gandhapudi, Woodward, & Orazio, 2011) Hsp70 is capable of activating T cells by inducing CD69 and IFN-γ, TNF-α, and other cytokines. (de Jong et al, 2014) Hsp90 is involved in TNF-α expression and nuclear factor kappa beta (NF-κB) signaling pathway activation in cytotoxic T cells. (Collins et al, 2014) Hsp27, Hsp90, Hsp110 and gp170 have been identified as antigens to induce immunity.(R.…”
Section: T-cell Activationmentioning
confidence: 99%